Study of Problems & Challenges of Rural House Improvement Project in Kermanshah County, Base of Attitude of Technical Supervisors - Aeizh Azmi; Akram Razlansari; Leila Mataei (تحقیقات کاربردی علوم جغرافیایی)
In this project government endow loam to villagers for improving their houses. This project help to villagers for improvement their life and it help to villagers for preparation for sudden hazards. Improvement rural houses project improve quality of life villagers. Therefore, this project presents for resolving problems and challenges that improvement rural houses project confront with them. Investigative method was descriptive-survey and we used from questionnaire for collecting data. Statistical society includes 50 people that we used from census method for sampling method. Statistical method was technical supervisors in Kermanshah County.  Reliability calculated by alpha Cronbach method that equal 0.72 and validity calculated by K.M.O and Bartlet method that equal (K.M. O=74/0) and Bartlet significant equal (0.0).  But technical supervisors have positive attitude about housing foundation of Islamic revolution performance. They were satisfaction from workshops and upstream supervisors in housing foundation of Islamic revolution of province of Kermanshah. Results shows that there is relationship between distance village from city and quality of building materials quality. Also, there is relationship between knowledge of people about project and time periods. It shows that knowledge people increase. Finally, by factor analysis we understand that there are 5 components that effect on improvement rural houses projects that include: dimension of individual people and technical supervisors, attitude of people to improvement rural houses projects, life quality and improvement in life style, challenge in law and discipline and time of project. They explain 65.85% of total of variance. Also, the findings show that there is a meaningful and reverse relationship between the beginning of the technical observer's period and the amount of his attention to the consciousness of the people at the level of 0/05. Meanwhile, people's awareness has increased over time.